Online-HPLC strategies, antioxidant and enzyme inhibitory activities of different extracts of mondia whitei leaves - Ahmed, Shakeel; Sinan, Kouadio Ibrahime; Nilofar, Claudio; Ferrante, Claudio; Eyupoğlu, Ozan Emre; Etienne, Ouattara Katinan; Zengin, Gökhan (Biolife Sas, 2023)
Background: Mondia whitei, an indigenous African plant, is widely recognised for its medicinal properties. Throughout ancient times, African communities have employed this remedy to address a wide range of health conditions. However, there is a lack of online High-Performance Liquid Chromatography (HPLC) studies available for this plant. The present investigation aimed to address and alleviate this deficiency by providing a comprehensive analysis.Methods: Methanol, combination of water and methanol, ethyl acetate, and water extracts of Mondia whitei (M. whitei) leaves were utilized in this study. The phenolic and flavonoids composition of the extracts determined by Folin-Ciocalteu and Aluminum chloride (AlCl3) assays, respectively. The antioxidant potential of all the extracts was assessed through a range of in vitro assays, including FRAP (Ferric reducing antioxidant power), DPPH (2,2-diphenyl-1-picrylhydrazyl), ABTS [2,2 '-Azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid)], CUPRAC (cupric reducing antioxidant capacity), PBD (phosphomolybdenum), and MCA (metal chelating ability). Subsequently, the online HPLC-linked system had established to compare these extracts using four distinct antioxidant analysis methods: FRAP, DPPH, ABTS, and CUPRAC. The enzyme inhibitory properties were also investigated against cholinesterases, tyrosinase, alpha-amylase and alpha-glucosidase.Results: The methanol-water and methanol extracts had the highest phenolic contents and demonstrated superior efficacy as scavenging/reducing agents and enzyme inhibitors, particularly against tyrosinase and cholinesterase (p < 0.05). Through the utilisation of various online HPLC antioxidant techniques, the identification of four molecules exhibiting antioxidant activity was achieved. These compounds were identified as Coumarin, Vanillin, p-OH benzoic acid, and Chlorogenic acid.Conclusions: Mondia whitei leaves can be regarded as a valuable source of natural bioactive compounds, with the potential to serve as a material basis for pharmacological effects in nutraceutical and pharmaceutical applications.
Keywords: Mondia Whitei; Online HPLC Assays; Antioxidants; Enzyme Inhibitors